Fourteenth century England. - Green, David; Given-Wilson, Chris (Fourteenth century England, 2019)
The essays collected here engage with many of the most important themes and subjects of the period. In addition to addressing matters of kingship and changing theories of power, they tackle questions concerning loyalty and rebellion at the centre of authority and on its margins; the role of law, both domestic and international; the nature of memory - legal, historical and fabricated; and the relationship between the Plantagenets and the rulers of those nations and territories over which England claimed dominion. In so doing, the collection offers important new insights into political and social developments at times of major turmoil, including Edward I's war with Scotland, the deposition of Edward II, and the Peasants' Revolt of 1381, while also exploring the mechanisms used to ensure peace and the smooth-running of a kingdom during a time of immense change